Highly efficient blue emitting one dimensional lead-free nanocrystals. Issue 31 (21st July 2022) - Duan, Jianing; Xi, Jun; Jiao, Bo; Dai, Jinfei; Zu, Yanqing; Wu, Zhaoxin
Abstract : Cs5 Cu3 Cl6 I2 nanocrystals exhibit a blue light emission with a high PLQY of 73.7%. Multiple self-trapped excitons are proposed to be responsible for the peculiar emission originating from various Cu–Cu interactions on one-dimensional chains. Abstract : Cesium copper halide perovskite-like nanocrystals (NCs) have emerged recently due to their nontoxicity and highly efficient and peculiar optoelectronic properties; however, this field is far from being quested yet. In this study, Cs5 Cu3 Cl6 I2 NCs in a one-dimensional chain structure are proposed by a modified hot injection method for the first time. The as-synthesized highly even Cs5 Cu3 Cl6 I2 NCs yield a blue emission at 464 nm, coupling a high photoluminescence quantum yield (PLQY) of 73.7%. The large Stokes shift of 186 nm and broadband emission demonstrate the existence of self-trapped excitons in Cs5 Cu3 Cl6 I2 NCs under UV excitation. Unlike the zero-dimensional prototype, one-dimensional chains consist of different polyhedron connection fashions, fostering their unique luminescent properties. We found Cs5 Cu3 Cl6 I2 NCs possess an asymmetric PL emission peak prevailing in a broad temperature range, highly correlating to abnormal multiple self-trapped excitons at 2.95 eV, 2.69 eV, and 2.53 eV, respectively. Interrogating the fundamental, triple Cu–Cu interactions originating from various polyhedral connection ways of one-dimensional chains are responsible for the hybrid excitonic states. This work establishes a rising class of lead-free NCs as an eligible candidate for stable functional device application and illustrates the fundamentals underlying the dissimilar excitonic properties of one-dimensional copper halides.